The Methodology to Evaluate a Rescue and Training Phantom for the Road Rescuing Organized by Police Officers as Exemplified by Crash Kelly - Pawel Gromek; Mariusz Nepelski (Communications - Scientific letters of the University of Zilina, 2021)
The paper presents a methodology to evaluate a rescue and training phantom for road rescuing organized by Police officers. The methodology is exemplified by the Crash Kelly phantom, static and dynamic functionalities of which seem to be more frequently implemented in the road safety training processes. It stems from a morphological analysis, focusing on the quality of rescue activities, emergency resources’ adequacy and the training levels. In addition, experts’ evaluation allows to examine phantoms using 6 practically determined criteria, expressing their strengths and weaknesses in analysed context.The results introduce Crash Kelly as a reference training equipment for Police officers dedicated to rescue victims after the road accidents. Basing on the research results, practical training guidelines are formulated.